Urban mobility practices and family proximity - Cosacov Martinez, Natalia (2019)
Through analyzing residential and daily mobility practices from a qualitative approach, this paper shows that families sustain a residential pattern by which they value and pursue proximity to relatives. This residential rationale prioritizes living nearby rather than living together. The families examined throughout the study maintain family residential proximity at the intra-urban and even intra-neighborhood levels. The article accounts for and examines the residential trajectories that uphold proximity to family members and their interactions with urban dynamics. Finally, it shows the significant role of family in achieving homeownership, which does not always contribute to the geographic aggregation of relatives.